An analysis on the service quality performance by Seri Warisan Resort / Rosdadawiyad Omar - Omar, Rosdadawiyad (Faculty of Business and Management, 2006)
This research is study on service quality at Seri Warisan Resort. Service is an act or performance that creates benefit for customers by bringing about a desired change in or on behalf of-the recipient. Quality is the degree to which a service satisfies customers by meeting their needs, wants and expectation. The objectives of the research are to know the customer awareness, to know the level of service and know the guest perception on the service provided. This study identifies the four hotel factors which are staff service quality, general amenities, room quality and value. The data are collected by distributed 100 questionnaires to 100 respondents. Respondents are the guests who visit the resort. A questionnaire with five-point Likert Scale is applied to measure customer satisfaction. Data is analyzed using SPSS software by frequency distribution, mean and cross tabulation. For the finding of this study, most of Seri Warisan Resort guest, feel moderate with the service provided. In order to achieve the guest expectation, Seri Warisan Resort can improve their service time to time.